Subtitling Norms: a Comparative Study of Iranian and American Films - Jabbarzadeh, Fatemeh (Iranian Journal of Translation Studies, 2007)
The present study investigates the application of norms in subtitling of some Iranian and American films. The questions this study seeks to answer are: what norms are applied in subtitling of Iranian and American films? And what are the similarities and differences between the norms applied in subtitling of Iranian and American films? In this article, a short theoretical discussion will be given about the main topics: audiovisual translation, especially subtitling, and norms. The material for the study consists of 5 Iranian films subtitled in English and 5 American films subtitled in English. Considering translation as a norm-governed activity, the researcher's main concern has been studying norms applied in the translation of some challenging concepts including culture-specific items, verbal visual signs and language varieties. By nature, this research is descriptive which is aimed at comparing the Iranian and American subtitled films with the focus on normative patterns governing their translation process. As in the field of translation studies norms are frequently used patterns, through this research some patterns applied by translators in the course of translating challenging concepts were extracted. The extracted patterns are: 1. the informal form is replaced by formal one; 2. the social dialect is rendered as it is uttered; 3. the local dialect is identified in brackets; 4. the CS item is replaced with a proper target CS item; 5. the CS item is manipulated to be understandable; 6. the CS item is preserved intact; 7. the CS item is omitted; 8. Verbal-visual signs are not subtitled; 9. songs are subtitled; 10. songs are not subtitled. Through this research the extracted patterns were considered the basis for analyzing the instances existing in the selected films.